Integrating business, social, and environmental goals in open innovation through partner selection - Santos, Ricardo (2022)
Although collaborative networks (CN) are widespread in academia and have come to be even more used in corporations all over the world, they still face several challenges on behalf of the new product development (NPD) context, especially in regard to the selection of the CN’s right partner. This becomes even more evident when it comes to promoting sustainable development goals within a CN’s activities, by selecting the right partners with a wide consensus from a CN’s management board, avoiding, therefore, the subjectivity around managers’ perception of a CN’s partner selection. Therefore, this work attempts to answer this problem, by presenting a soft-computing-based framework, to support the managers’ board on partner search and selection. The method presented here is further assessed by using a case study, based on the development of a green product, where, according to the obtained results, it is demonstrated that the proposed approach is extremely effective for partner selection, by assessing and prioritizing each candidate involved. The most suitable candidate that fulfills the CN’s requirements is then selected to be integrated as a future partner.